Mengkaji Karakteristik Media Televisi untuk Memudahkan Merancang Komunikasi Visual yang Tepat - Tunjung Riyadi (Bina Nusantara University, 2010)
A work of visual communication design which aired on the television screen has a different perspective in its interpretation in the eyes of the audience when compared to other media. By understanding the characteristics and nature of media, proper exploration of graphic design can easily be created. Through literature study, observations of the author as a practitioner of graphic design for television and comparisons with the print media will facilitate the understanding of this study.